Identity Using in Public Relations for Wat Lam Phaya Floating Market Tourism Lam Phaya Sub-district, Bang Len District, Nakhon Pathom Province - Pratumsuwan, Kesinee; Sirinthnathorn, Natcha; Sujittavanich, Marisa; Sarbmuangpak, Tivaporn; Boonkong, Vinai; Nachaidee, Virasak; Namoonmong, Nuchjaree (Ratchaphruek Journal, 2020)
The objectives of this quantitative research were to study 1) media exposure behavior and tourism behavior of tourists, 2) motivation level due to identity, and 3) relationship between personal factors and motivation level due to identity of Wat Lam Phaya floating market. The samples were 400 tourists visiting Wat Lam Phaya floating market, chosen by convenience sampling during January and February 2020.The research instrument used for data collection was questionnaire. Statistics used in data analysis were percentage, mean, standard deviation, t-test, one- way ANOVA, and content analysis. The findings showed that most tourists were female, 31-40 years old, Bachelor degree holders, company employees, income 10,001-20,000 baht/month. They mostly received the floating market information from their friends or folks. Its content was about food, natural place and gift or souvenir. Most of them travelled there 2-3 times a year, with their families or relatives, by their own cars, on the weekends, duration 1-3 hours, and spent500-1,000 baht for a trip. Obviously, main purposes to visit the floating market were for food, relaxation and spending. Motivation level due to identity of the floating market as overall was at a high level. The relationship between personal factors and motivation level found that tourists with different gender, level of education, occupation and income, motivation level due to identity of the floating market was different statistically significant at .05.